2023
DOI: 10.1093/ibd/izad065
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: The Association Between Serum Ustekinumab Trough Concentrations and Treatment Response in Inflammatory Bowel Disease

Abstract: Background Optimizing therapy and monitoring response are integral aspects of inflammatory bowel disease treatment. We conducted a systematic review and meta-analysis to determine whether serum ustekinumab trough concentrations during maintenance therapy were associated with ustekinumab treatment response in patients with inflammatory bowel disease. Methods A systematic review was performed to March 21, 2022, to identify stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The average post-operative HBI was signi cantly lower in the adequate ustekinumab group compared to the suboptimal group. This is in line with previous data showing that higher ustekinumab levels are associated with higher rates of clinical remission de ned as HBI < 5 [29]. Our study showed no difference in endoscopic scores (SES-CD or Rutgeerts) between the suboptimal and adequate ustekinumab level groups.…”
Section: Discussionsupporting
confidence: 93%
“…The average post-operative HBI was signi cantly lower in the adequate ustekinumab group compared to the suboptimal group. This is in line with previous data showing that higher ustekinumab levels are associated with higher rates of clinical remission de ned as HBI < 5 [29]. Our study showed no difference in endoscopic scores (SES-CD or Rutgeerts) between the suboptimal and adequate ustekinumab level groups.…”
Section: Discussionsupporting
confidence: 93%
“…Role of TDM: Despite some contrary findings regarding the association between trough levels and Crohn’s disease response (clinical or biochemical)[ 119 - 123 ], there is robust evidence to suggest that ustekinumab trough levels correlate with clinical, biomarker and/or endoscopic response in Crohn’s[ 124 - 139 ]. This was confirmed in meta-analysis which showed higher median ustekinumab trough concentrations occur in individuals who achieve clinical remission compared with those who do not achieve remission[ 140 ].…”
Section: Resultsmentioning
confidence: 76%
“…However, despite these findings the role of TDM to guide ustekinumab therapy is limited. The significant variations between studies in reported ustekinumab levels to achieve response in conjunction with the heterogeneity in methods of reporting ustekinumab levels do not currently permit a clear cutoff value for defining a response to therapy[ 140 ]. Furthermore, there is only sparse data evaluating ustekinumab levels following dose escalation[ 110 , 123 , 133 , 141 ] and endoscopic remission was associated with an increase in ustekinumab levels in only one of these observational studies[ 133 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immunogenicity was noted to be low in the pivotal phase 3 trials for ustekinumab in both UC and CD [40]. A systematic review estimated the rate of ADA development on maintenance therapy to be between 4.2% and 5.6% [42]. It has been suggested that immunogenicity is transient with ustekinumab [40]; however, a recent study has shown that it may correlate to loss of response [43].…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…The majority of these studies evaluated serum trough levels via ELISA at the time of ustekinumab induction or mobility shift assay and at follow-up periods up to week 26. The identified target trough levels required on maintenance therapy to achieve a clinical response have varied substantially [42], with levels as low as 1.3 µg/mL [40] and up to levels of 4.5 µg/mL [15] being observed as targets to establish clinical response. The timing of drug level measurement is also likely to have an impact on these reported drug levels and may explain some of the variation in identified cut-off values [46].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%